PEMBERIAN TEKNIK RELAKSASI NAPAS DALAM PADA PASIEN PENDERITA HIPERTENSI DENGAN MASALAH NYERI AKUT - Oktary, Nuraisyah; Putri, Zaenab; Batubara, Khairunnisa (LPPM AKPER GITA MATURA ABADI KISARAN, 2025)
Hypertension is a condition where systolic blood pressure is more than 140 mmHg and diastolic blood pressure is more than 90 mmHg, which often causes complications, one of which is headache, so it is necessary to provide deep breathing relaxation techniques. Deep breathing relaxation is done by taking a deep breath through the nose, letting it fill the stomach, then exhaling slowly through the mouth for about 3-5 times, this helps reduce pain and lower stress hormone levels. The aim of this scientific paper is to provide non-pharmacological therapy with deep breathing relaxation techniques for hypertension patients with acute pain problems. The research method design is a descriptive case study accompanied by Wong-Baker pain scale measurements. The research sample is 2 elderly patients.The results of the study after administering deep breathing techniques to the first patient showed a decrease in pain with an initial scale of 6-7 until the patient did not feel pain and in the second patient the decrease occurred from a scale of 4-5 until there was no more pain. So it can be concluded that this deep breathing technique has an effect on reducing pain. Deep breathing relaxation techniques taught to patients can have a significant effect in reducing the level of pain experienced by patients with hypertension with pain problems.